FREQUENCY RESPONSE TEST AND FIELD TEST OF MEMS ACCELEROMETER AS A CHEAPER AND LIGHTER SEISMIC SENSOR - Rahadian Budi, Fakhri
Although favorable for oil & gas exploration or geotechnical application, the required seismic sensors for ground vibration measurement are usually expensive and heavy. Several researchers have reported the high performance nature of commercially available Micro-Electro-Mechanical Systems (MEMS)-based accelerometer as cheaper and lighter seismic sensors. This research aims to evaluate frequency response and field performance of ADXL335 accelerometer. Frequency response test was done on 10 – 100 Hz range, and will be presented as a plot of sensitivity (V/ms-2) versus frequency. A subwoofer was used to simulate sinusoidal movement on a tested accelerometer with a controlled frequency, along with a 10 Hz traditional geophone as a reference. Geophone’s maximum signal gives maximum velocity of the sinusoidal movement, thus by utilizing simple harmonic oscillation equation, maximum acceleration of sinusoidal movement (and later MEMS accelerometer’s sensitivity) could be acquired. High resolution oscilloscope was used on to record MEMS accelerometer and reference geophone output signal during frequency response test. Field test was done using three identical accelerometers with ±40 cm spacing, using sledgehammer to generate seismic wave and 16-bit seismograph to record detected ground vibration. Frequency response test shows relatively constant responses 10 – 100 range (±3 dB tolerance towards static sensitivity), proving MEMS accelerometer’s wide bandwidth and superiority in measuring low frequency vibrations. Field test shows accelerometer’s ability to smoothly integrate with a seismograph and detect surface wave in field setting. However, field test also shows one of tested MEMS accelerometer’s weakness, which is its low sensitivity.